Consuming use orientated product service systems: A consumer culture theory perspective. (10th January 2017) - Catulli, Maurizio; Cook, Matthew; Potter, Stephen
Abstracts: Research suggests that product service systems (PSS) may usefully form part of the mix of innovations necessary to move society toward more sustainable futures. However, PSS implementation rates are disappointingly low and an implementation gap has emerged. Drawing on consumer culture theory (CCT), this paper provides insights to help resolve this issue in business to consumer markets. Since consumption of use orientated PSS is analogous to access based consumption, six dimensions of access are set out to analyse a case study of infant car seat provision. Five outcomes are derived from the analysis and these include partial identification with accessed product and interplay of use and symbolic value. This analysis questions the view that PSS do not create sufficient value to overcome a preference for ownership in western societies. Rather, PSS consumption is likely to arise when both functional and symbolic value are extracted by consumers and when PSS are promoted to appropriate consumer groups such as 'nomads'. Further research is needed to explore these phenomena and address the issues they raise in PSS design processes. Highlights: Investigates implementation gap of product service system (PSS) in consumer markets. Empirical study of infant care equipment PSS. Explores consumption of PSS through the lens of consumer culture theory (CCT). Discusses the functional and symbolic value consumers can extract from PSS. Proposes consumer groups such as 'nomadic consumers' as possible recipients of PSS.